Perancangan Company Profile SMKN 3 Kota Solok Menggunakan Macromedia Director - Safira, Laila; Jeprimansyah, Jeprimansyah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
By utilizing multimedia technology, this research has produced an interactive and engaging video profile for SMK Negeri 3 Kota Solok. This video was created using Macromedia Director software. The objective is to increase awareness of the school among prospective students and the community. The video showcases various important information such as available study programs, school facilities, and achievements. With this video profile, it is expected that more students will be interested in enrolling at SMK Negeri 3 Kota Solok. The video production process involved several stages, starting from data collection, video design, to video editing using the software. The final outcome of this research is expected to be an effective promotional tool for the school